The Frame of Islam in Multicultural Education at Kinderglobe Kindergarten - Maftuhah, Maftuhah; Raswan, Raswan (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This research is based on recognizing the Islamic concept of multiculturalism and multicultural coaching in Kinderglobe Kindergarten, where the people involved in the kindergarten (principals and teachers) have a thick Islamic background and experience. This research aims to know the pattern of multicultural development and religious reasons used in multicultural development at Kinderglobe Kindergarten. This qualitative case study, using an analytic descriptive method, was conducted at Kinderglobe Kindergartens in two locations, in Pamulang Tangerang Selatan City of Banten Province and Gunung Sindur of Bogor Regency. Data were collected using observation, interviews, and documentation. They were analyzed using the interactive model of Miles et al., i.e., data collection, data condensation, data display, and conclusion. The data, then, were validated using the triangulation technique. The results showed that multicultural coaching was implemented intentionally and planned through the activities in the class (curricular) and outside the class (non-curricular). For religious reasons, multiculturalism is part of Islamic values, and practicing multicultural education is part of da'wa bil hal. This da’wa bil hal is also called multicultural da’wa because it is practiced in a multicultural society. The research implies that da’wa bil hal must be implemented in children's education because it is fundamental to develop their personality in a plural society.